EFEKTIVITAS SISTEM INFORMASI DAN KOMPUTERISASI HAJI TERPADU (SISKOHAT) DALAM PENYELENGGARAAN IBADAH HAJI DI KABUPATEN SIDENRENG RAPPANG - Mulhaeriyah Mulhaeriyah; Nurjannah Nonci; Ahmad Mustanir (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze the effectiveness of the Integrated Hajj Information and Computerization System (SISKOHAT) in the implementation of Hajj services in Sidenreng Rappang Regency. The analysis focuses on three aspects: the implementation of the system in improving service productivity and quality, the responsiveness and responsibility of officers in managing digital-based services, and the accountability and fairness of public services through SISKOHAT. This research employs a descriptive qualitative method with in-depth interviews involving 20 informants, consisting of SISKOHAT operators, prospective Hajj pilgrims, and other related stakeholders. The findings indicate that SISKOHAT makes a significant contribution to accelerating administrative processes, minimizing data input errors, and enhancing service transparency. However, the system’s effectiveness remains limited by technical constraints, such as network disruptions, inadequate facilities and infrastructure, and low technological literacy among some officers and pilgrims. The study highlights the need to strengthen human resource capacity, improve technological infrastructure, and reinforce monitoring mechanisms to ensure effectiveness, accountability, and fairness in digital-based Hajj administration at the regional level.